PROSPEK PENGEMBANGAN KOMODITAS KOPI ROBUSTA DI PT. KALIPUTIH KECAMATAN LEDOKOMBO KABUPATEN JEMBER - Merry Tri H.S; Sugeng Raharto; Titin Agustina (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
One of private plantation in Jember is PT. Kaliputih located in Ledokombo that founded since 1966. The Activity conducted by PT. Kaliputih cannot be separated by many problem faced, namely: the weather conditions and uncertain climate, the high fluctuation of the price of coffee, low crop production under normal potency, harvest and post-harvest processing which is less than the maximum. This study aimed (1) to determine the trend of coffee logs production from 2014 to 2024 at PT. Kaliputih Ledokombo Jember, (2) to determine the factors that affect the level of income of ose coffee at PT. Kaliputih Ledokombo Jember, (3) to determine the prospects of development of robusta coffee at PT. Kaliputih Ledokombo Jember. Method of determining the area of research is conducted on purpose (purposive method). The research method used is descriptive, analytic, and correlational. The data collection method in this study using interviews and literature. Data analysis of production trends, multiple linear regression, and SWOT. The results showed that (1) the trend in production period 2014-2024 increased by 5193.28 kg , (2) the factors that significantly affect the earnings of coffee ose at PT. Kaliputih is the amount of production and the selling price, (3) prospects for the development of robusta coffee at PT. Kaliputih is on the position prospective. Keywords : Coffee, trend production, SWOT